(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
We studied in this work the applicability of Laplace decomposition method (LDM) and modified Laplace decomposition method (MLDM) of differential-difference equations of order (2,1), which means the differential equation is of order 2 and the difference equation is of order 1. Finally, we give two illustrative examples to show the applicability and the effectiveness of the methods above